Equivalência de métodos alternativos ao oficial para determinação de Salmonella Enteritidis e Typhimurium em amostras ambientais avícolas - Coelho, Letícia Ríspoli (2012)
The infection of humans with Salmonella, particularly by serovars Enteritidis and Typhimurium is a worldwide public health concern. The analysis of this pathogen in birds feces and environment is a way to monitoring the infection in batches and to verify the need of introduction of controls, with recommendation of European Commission Regulation (EC) (No. 646/2007) that lots of birds are being analyzed for the presence of these serovars in phases prior to slaughter. Different methodologies can be used to research these microrganisms in environmental samples, however, most of them demands a long time to obtain the results. Thus, it is desirable that other methods, faster and more practical have their performance verified for possible deployment in routine. The aim was to evaluate the equivalence between the results obtained by the methods: BAX ®, Half Semi-solid Rappaport- Vassiliadis Modified (MSRV) (ISO 6579) method and the traditional official reference in Brazil (Ordinance 126, MAPA) for Salmonella Typhimurium and S. Enteritidis in poultry environmental samples. Prope and feces samples fortified with an average of 100 to 1000 CFU/g of each serovar, and the same samples were evaluated without fortification by the three methods. Were obtained 504 diagnoses that were analyzed for the same repeatability, reproducibility, sensitivity, specificity and accuracy. These indices were conducted individually and in relation to the traditional method (relative rates). The results indicated that the methods analyzed showed satisfactory performance and compliance testing verified the correspondence between the alternative methods and official method, which allow us to affirm that the methods have equivalent performances.